Genetic basis of depressive disorders - Yu. D. Davydova; R. F. Enikeeva; A. V. Kazantseva; R. N. Mustafin; A. R. Romanova; S. B. Malykh; E. K. Khusnutdinov (Вавиловский журнал генетики и селекции)
Depression is a common mental disorder being one of the main causes of disability and mortality worldwide. Despite an intensive research during the past decades, the etiology of depressive disorders (DDs) remains incompletely understood; however, genetic factors are significantly involved in the liability to depression. The present review is focused on the studies based on a candidate gene approach, genome-wide association studies (GWAS) and whole exome sequencing (WES), which previously demonstrated associations between gene polymorphisms and DDs. According to the first approach, DD development is affected by serotonergic (TPH1, TPH2, HTR1A, HTR2A, and SLC6A4), dopaminergic (DRD4, SLC6A3) and noradrenergic (SLC6A2) system genes, and genes of enzymatic degradation (MAOA, COMT). In addition, there is evidence of the involvement of HPA-axis genes (OXTR, AVPR1A, and AVPR1B), sex hormone receptors genes (ESR1, ESR2, and AR), neurotrophin (BDNF) and methylenetetrahydrofolate reductase (MTHFR) genes, neuronal apoptosis (CASP3, BCL-XL, BAX, NPY, APP, and GRIN1) and inflammatory system (TNF, CRP, IL6, IL1B, PSMB4, PSMD9, and STAT3) genes in DD development. The results of the second approach (GWAS and WES) revealed that the PCLO, SIRT1, GNL3, GLT8D1, ITIH3, MTNR1A, BMP5, FHIT, KSR2, PCDH9, and AUTS2 genes predominantly responsible for neurogenesis and cell adhesion are involved in liability to depression. Therefore, the findings discussed suggest that genetic liability to DD is a complex process, which assumes simultaneous functioning of multiple genes including those reported previously, and requires future research in this field.